2003
DOI: 10.1590/s0102-86502003000600011
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do omeprazol e do pantoprazol sobre a regeneração hepática após hepatectomia parcial em ratos

Abstract: Melo GB, Silva RL, Fakhouri R, Melo VA, Lima SO. Efeito do omeprazol e do pantoprazol sobre a regeneração hepática após hepatectomia parcial em ratos. Acta Cir Bras [serial online] 2003 Nov-Dez;18(6). Disponível em URL: http://www.scielo.br/acb. RESUMO -Objetivo: Avaliar os efeitos do omeprazol e do pantoprazol sobre a regeneração hepática após hepatectomia parcial. Métodos: Cinqüenta e oito ratos Wistar machos foram divididos em 4 grupos: Grupo SHAM, Grupo HP, Grupo PANTO e Grupo OMEP. Eles foram submetidos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Histological analysis in liver tissue demonstrated that there was alterations in the cell renewal. Hepatocytes are rarely found in mitosis, although cell proliferation can occur by chemical and physical stimuli and in the presence of exogenous substances, which can have a deleterious effect and lead to cell death (Melo et al., 2003). The maintenance of liver functions is conferred by the cellular integrity, as well as the hepatic parenchyma (Melo et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histological analysis in liver tissue demonstrated that there was alterations in the cell renewal. Hepatocytes are rarely found in mitosis, although cell proliferation can occur by chemical and physical stimuli and in the presence of exogenous substances, which can have a deleterious effect and lead to cell death (Melo et al., 2003). The maintenance of liver functions is conferred by the cellular integrity, as well as the hepatic parenchyma (Melo et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocytes are rarely found in mitosis, although cell proliferation can occur by chemical and physical stimuli and in the presence of exogenous substances, which can have a deleterious effect and lead to cell death (Melo et al., 2003). The maintenance of liver functions is conferred by the cellular integrity, as well as the hepatic parenchyma (Melo et al., 2003). Our results showed that the highest dose of AEG was able to reduce the mitotic index (Figure 6) and did not lead to significant changes in the necrosis levels.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Adhikay et al 32 used a dose of 3 mg/kg in rats with a view to curing gastric ulcers that had been induced. In 2003, Melo et al 33 subjected Wistar rats to intake 0.2 mg/kg, with the aim of evaluating the effect of this intake on partial hepatectomy. Even though many dosages have been observed, there is no consensus in the literature on animal experiments regarding the PPI dose that would be equivalent to those used in humans, for the purpose of long-term testing.…”
Section: Discussionmentioning
confidence: 99%
“…Melo et al, (2003) Os antioxidantes naturais também são estudados para a quimioprevenção do câncer, assim o guaraná Paullinia cupana, planta originária do Brasil, possui alta concentração de tanino, produto secundário do metabolismo de várias plantas e que pode suprimir a carcinogênese química induzida pelo N-nitrosodietilamina (DESHPANDE et al, 1984;FUKUMASU et al, 2006). Estudos realizados com animais de criação têm demonstrado os efeitos benéficos da suplementação de dietas com antioxidantes sobre a produção e a qualidade dos produtos gerados.…”
Section: Estudos Realizados Com O óLeo De Orégano Demonstraram Ação Aunclassified